Bobsleigh and skeleton - Sabbioni, E.; Melzi, S.; Cheli, F.; Braghin, F. (The engineering approach to winter sports, 2016)
The text gives a complete overview about the bobsleigh and the related discipline of skeleton. Some analyses will also be extended to luge. It gives also an overview about the history of this disziplines.